Mixed methods in business and management: A call to the ‘first generation’ - Cameron, Roslyn (eContent Management, 2011)
Mixed methods is a youthful but increasingly robust methodological movement characterised by:a growing body of trans-disciplinary literature; prominent research methodologistslauthorities; theemergence of mixed method specific journals, research texts, and courses; a growth in popularityamongst research funding bodies. Mixed methods is being utilised and reported within business andmanagement fields, despite the quantitative traditions attached to certain business and managementdisciplines. This paper has utilised a multistrand conversion mixed model research design toundertake a retrospective content analysis of refereed papers (n = 281) from the 21st Australian andNew Zealand Academy of Management (ANZAM) Conference 2007. The aim of the study is toprovide a methodological map of the management research reported at the conference, and in particularthe use, quality and acceptance level of mixed methods research within business and managementfields. Implications for further research are discussed along with a call to the 'first generation'of business and management mixed method researchers to instigate mixed methods research trainingand capacity building within their respective business schools, relevant academies and associatedprofessional forums and publications.